2016
DOI: 10.1039/c6ra03086f
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of imidazolium based ionic liquids with Triton X-100 micelles: investigating the role of the counter ion and chain length

Abstract: Size and shape of Triton X-100 micelles can easily be controlled by the appropriate selection of ionic liquids with varying hydrophobicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 82 publications
3
6
0
Order By: Relevance
“…Another sample studied in this same manner showed the same results. These findings correlate well with the literature data on the adsorption of surfactants on hydrophobic surfaces. Aqueous dispersions of nanocapsules investigated here were stabilized by Triton X-100 without removal of the inner surfactant layer. Under these conditions, one may expect a single layer of Triton X-100 outside and a single layer of residual SDBS/CTAT mixture on the inside of the shell.…”
supporting
confidence: 91%
“…Another sample studied in this same manner showed the same results. These findings correlate well with the literature data on the adsorption of surfactants on hydrophobic surfaces. Aqueous dispersions of nanocapsules investigated here were stabilized by Triton X-100 without removal of the inner surfactant layer. Under these conditions, one may expect a single layer of Triton X-100 outside and a single layer of residual SDBS/CTAT mixture on the inside of the shell.…”
supporting
confidence: 91%
“…Reproducibility of measurements among multiple independently prepared samples suggested that the thickness of the surfactant layer remained constant under a specific preparation protocol and was reflective of the density of surfactants on the surface of the shells. The contribution to the total thickness due to adsorbed surfactants was in good agreement with literature data reporting the thickness of surfactant layers adsorbed on flat surfaces. In the data presented below, however, we chose not to subtract the thickness of the surfactant layer from the total thickness of the surfactant-supported shells so as to minimize processing the results and avoid introducing larger uncertainties.…”
Section: Resultssupporting
confidence: 77%
“…[C 12 mim]Cl and [C 10 mim]Cl are amphiphilic organic cations (with a long alkyl chain attached to an aromatic ring) associated with a small inorganic anion, and, because of their surfactant-like structures, it is expected that, when these ILs are mixed with aqueous solutions, they will form micelles and exhibit selfassembling behavior [31]. Thakkar and collaborators [37] demonstrated that [C 10 mim]Cl penetrates deeper into the Triton X-100 micellar core as a result of the long imidazolium alkyl chain. This phenomenon probably occurs when imidazolium-based ILs with long alkyl In all the systems, increasing the concentration of Triton X-114 led to high T cp values.…”
Section: Effects Of the Ils On The Binodal Curvesmentioning
confidence: 99%